The best cat ever - Amory, Cleveland (Polar Bear / Cleveland Amory, 1993)
The Best Cat Ever continues the life and times of the world-famous Polar Bear and his cranky, lovable cohort, Cleveland Amory. We shar Amory and Polar Bear's good times as Amory recalls his years at TV Guide and his experiences with various notables, including the Duke and Duchess of Windsor. And we share the trials and tribulations of this sublime cat versus his redoubtable owner - or rather, ownee. The wittiest and most poignant installment of the Polar Bear trilogy.